International agreements on access to genetic resources, main obligations for colombia (2001)
Genetic resources have acquired, in the last 20 years, strategic significance, not only due to their real or potential value, but also to their applications in several fields, such as research and industry. Different economic sectors have found in them a mechanism to meet the increasing demand, for example, in agriculture and pharmaceutical markets. On the other hand, it has become clear that these resources need to be used in such a way that sustainability and biodiversity be preserved. Other important issues have to do with their property. A rather polemical discussion has arisen in the international level regarding regulations that govern access to these resources in order to prevent impairing development and rather further the protection of biodiversity. This article aims at showing the international agreements so far reached on this matters, offering at the same time a clear overview of this subject.